To spend or not to spend? The case of defence expenditure in the context of the Greek crisis - Andreou, Andreas S.; Migiakis, Petros M.; Zombanakis, George A. (My University, 2014)
The aim of this paper is to evaluate the recipe that requires defence expenditure reductions in an environment of severe budget cuts together with rising costs. The case of Greece, a country that is in the process of recovering from a six-year economic crisis, provides an example of an economy in which an import – substitution strategy via the promotion of the Hellenic Defence Industrial Base potential can contribute to both economic growth and unemployment reduction, thus adding to the effectiveness of the import-substitution policies employed and compromising between an austerity programme and the defence needs of the country.
Keywords: Defence expenditure; Defence industrial base; Neural networks